No tech hacking a guide to social engineering, dumpster diving, and shoulder surfing - Long, Johnny (Syngress Elsevier Science [distributor], 2008)
As the clicȟ reminds us, information is power. In this age of computer systems and technology, an increasing majority of the world's information is stored electronically. It makes sense then that as an industry we rely on high-tech electronic protection systems to guard that information. As a professional hacker, I get paid to uncover weaknesses in those systems and exploit them. Whether breaking into buildings or slipping past industrial-grade firewalls, my goal has always been the same: extract the informational secrets using any means necessary. After hundreds of jobs, I discovered the secret to bypassing every conceivable high-tech security system. This book reveals those secrets, and as the title suggests, it has nothing to do with high technology. As it turns out, the secret isn't much of a secret at all. Hackers have known about these techniques for years.